PRIA-PRIA KINCLONG DI MEDIA SOSIAL: Telaah Semiotis terhadap Perangai Hedon di Kanal Instagram @Bangbenuachallenge - Rahayu, Rully Mondy Herdira (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2016)
This research analyzes how the practice of male hedonism on Instagram as a phenomenon, where the photos uploaded on Instagram become a way of communicating one's social class with the items they show on the photo. The phenomenon is shown on Pablo Putera Benua and social media Instagram @bangbenuachallenge account which will be used as subject and object of this research. This research uses descriptive qualitative study with semiolysis methodology Roland Barthes, where to find meaning depend on object of research use denotation, connotation and myth in analyzing signs of male hedonism on Instagram @bangbenuachallenge account. The results showed that the practice of male hedonism is constructed by the meanings of Instagram @banbenuachallenge account. The practice of male hedonism is represented by the myth of luxury brands symbolizing one's social status.